2023
DOI: 10.3389/fped.2023.1239423
|View full text |Cite
|
Sign up to set email alerts
|

Impact of vaccination with different types of rotavirus vaccines on the incidence of intussusception: a randomized controlled meta-analysis

Guoyong Wang,
Kaijun Zhang,
Rensen Zhang
et al.

Abstract: BackgroundIntussusception is a prevalent pediatric issue causing acute abdominal pain, with potential links to rotavirus vaccines. The variety of these vaccines has grown in recent years. This meta-analysis study aims to evaluate the impact of various rotavirus vaccines on intussusception incidence.MethodsWe executed a thorough search across databases like PubMed, Cochrane Library, Embase, and Web of Science, leading to the selection of 15 credible randomized controlled trials (RCTs) that encompass various typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…A growing number of studies have found that the introduction of rotavirus vaccine does not increase the incidence of intussusception ( 2 , 7 , 16 - 18 , 24 ). Wang et al ( 25 ) included 15 randomized controlled studies from different countries for the latest meta-analysis and found that rotavirus vaccination did not increase the incidence of intussusception, and there was no significant difference in the incidence of intussusception by subgroup analysis of different vaccine brands and types. More importantly, data from Korea and Japan ( 26 , 27 ) showed that the incidence of intussusception in children decreased after rotavirus vaccine introduction, suggesting that rotavirus vaccination may also have a protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have found that the introduction of rotavirus vaccine does not increase the incidence of intussusception ( 2 , 7 , 16 - 18 , 24 ). Wang et al ( 25 ) included 15 randomized controlled studies from different countries for the latest meta-analysis and found that rotavirus vaccination did not increase the incidence of intussusception, and there was no significant difference in the incidence of intussusception by subgroup analysis of different vaccine brands and types. More importantly, data from Korea and Japan ( 26 , 27 ) showed that the incidence of intussusception in children decreased after rotavirus vaccine introduction, suggesting that rotavirus vaccination may also have a protective effect.…”
Section: Discussionmentioning
confidence: 99%